The History of Reimbursements in Neurology - Lakhan, Shaheen E.; Abied, Amr M.; Tepper, Deborah; Nguyen, Truc (Frontiers in Neurology, 2013)
The Patient Protection and Affordable Care Act (PPACA) addresses consumer protection, employer-provided insurance coverage, as well as the government's role in providing health care access to the most vulnerable populations. Within the practice of neurology, the PPACA has the challenging goal of reconciling the needs of the growing elderly population with the financial barriers to costly yet available health care services. To bridge that gap, all health care professionals working in the field of neurology must reflect on the effect previous Medicare reimbursement policies have had on the current practice of neurology, and utilize lessons learned in recent years. The test of time will tell whether the PPACA will achieve the goal of decreasing in health care spending while ensuring quality universal healthcare services.